MSMEs Digitalization Strategy Increasing Sustainability in the Era of Digital Transformation - Zennanda Hilda Pratiwi; Muhammad Syaiful Umam (Clean and Sustainability Business, 2025)
Objectives: This research aims to explore strategies for improving the sustainability of micro, small, and medium enterprises (MSMEs) in the era of digital transformation by identifying the key factors and challenges businesses face in adopting digital technologies. Research Design & Methods: This research uses a qualitative approach with a literature review methodology to analyze existing studies and best practices related to digital transformation strategies and MSME sustainability. Findings: The research identified key aspects of sustainability that support the digital transformation process in MSMEs: digital presence, data analytics, process optimization, customer experience, and digital skills and training. Furthermore, sustainability practices such as adaptability, collaboration, risk management, continuous learning, scenario planning, crisis communication, and cybersecurity play an important role in ensuring business continuity in the digital age. Implications & Recommendations: The successful digital transformation of MSMEs requires a comprehensive approach that includes technology, digital skills, business innovation, and organizational culture. Policy support through regulations, incentives, and training is also a key factor in improving the readiness of MSMEs in the digital era.  Contribution & Value Added: This study presents a strategic framework for MSMEs in the face of digital transformation, helping to overcome challenges and promote sustainability. The findings contribute to the academic literature and guide practitioners, policymakers, and researchers.